Overview of Patients with Multiple Primary Tumors During Eighty-four Months Follow-up: A Single Center Experience - Özlem Mermut; Rıza Umar Gürsu (İstanbul Medical Journal, 2019)

(untitled)
Introduction:Advances in oncological diagnosis and treatment increase survival and remission of the disease. However, prolonged survival also increases the likelihood of developing second primary malignancies. The aim of this article was to evaluate whether the second primary tumor is associated with the first primary tumor and to determine the survival time in patients diagnosed with cancer, treated, and followed-up, and to make recommendations about the follow-up of these patients.Methods:Patients who were admitted to the İstanbul Training and Research Hospital, Clinic of Radiation Oncology and Medical Oncology, between January 2011 and December 2017, and who had a follow-up of more than 6 months were retrospectively reviewed. Of 9892 patients, multiple primary tumors (MPT) were detected in 121 patients. The origin of tumor, occurrence time, gender, age, metastasis and survival rates of the patients were investigated. Data were collected using Excel and transferred to SPSS 22.0 program.Results:There were 56 (46%) female and 65 (54%) male patients. The mean age of the female patients was 58 years and the mean age of the male patients were 64 years. The median age for both sexes was 63 (range: 37-82). The second primary tumor was found to be metachronous in 89 patients (74%) and synchronous in 32 patients (26%). The incidence of MPT was 1.22%. Breast-breast cancer pair in women and larynx-lung cancer pair in men were in the foreground. Eighty-one patients (67%) had a history of smoking and 18 patients (15%) had a history of alcohol use. In synchronous and metachronous tumors, the most common metastasis was observed in the skeletal system. Median overall survival was 51 months in synchronous tumors and 72 months in metachronous tumors.Conclusion:The development of a second primary cancer in a patient diagnosed with cancer is higher than in those who have not been diagnosed with cancer. Early diagnosis of patients and prolongation of survival may increase the incidence of second primary tumors. For this reason, new complaints emerging during the follow-up of patients diagnosed with cancer should be considered and second primary tumors should be suspected. We think that long-term follow-up, especially for detecting early metachronous tumors, will contribute to survival in patients with cancer.